A review of recent progress on laser-plasma acceleration at kHz repetition rate - Faure, J; Gustas, D; Guénot, D; Vernier, A; Böhle, F; Ouillé, M; Haessler, S; Lopez-Martens, R; Lifschitz, A (Plasma physics and controlled fusion, 2019)
We report on recent progress on laser-plasma acceleration using a low energy and high-repetition rate laser system. Using only few milliJoule laser energy, in conjunction with extremely short pulses composed of a single optical cycle, we demonstrate that the laser-plasma accelerator (LPA) can be operated close to the resonant blowout regime. This results in the production of high charge electron beams (>10 pC) with peaked energy distributions in the few MeV range and relatively narrow divergence angles. We highlight the importance of the plasma density profile and gas jet design for the performance of the LPA. In this extreme regime of relativistic laser-plasma interaction with near-single-cycle laser pulses, we find that the effect of group velocity dispersion and carrier envelope phase can no longer be neglected. These advances bring LPAs closer to real scientific applications in ultrafast probing.